The Spatial Distribution of Dermacentor Ticks (Ixodidae) in Germany—Evidence of a Continuing Spread of Dermacentor reticulatus - Drehmann, Marco; Springer, Andrea; Lindau, Alexander; Fachet, Katrin; Mai, Sabrina; Thoma, Dorothea; Schneider, Carina R.; Chitimia-Dobler, Lidia; Bröker, Michael; Dobler, Gerhard; Mackenstedt, Ute; Strube, Christina (Frontiers in Veterinary Science, 2020)
In Europe, two tick species of the genus Dermacentor occur, Dermacentor marginatus and Dermacentor reticulatus. When the spatial distribution of both species in Germany was studied comprehensively for the first time in 1976, D. marginatus populations were recorded along the Rhine and Main river valleys in southwestern Germany, while D. reticulatus was very rare. In the last 50 years, however, a considerable range expansion of D. reticulatus has been noted in several European countries. To assess the current distribution of Dermacentor spp. in Germany, citizens were asked to send in ticks suspected to belong to the genus Dermacentor or that were of "unusual" appearance. From February 2019 until February 2020, 3902 Dermacentor ticks were received in total. Of those, 15.48% (604/3902) were identified as D. marginatus and 84.24% (3287/3902) as D. reticulatus, while eleven specimens could not be identified to species level. The majority of D. reticulatus specimens was collected from dogs (1212/2535; 47.12%) while D. marginatus was mostly collected from horses (184/526; 34.98%). Our results confirm that the adults of both Dermacentor species are active all year round. Dermacentor reticulatus specimens were sent in from all federal states except the Free and Hanseatic city of Hamburg, while D. marginatus specimens were only received from locations in southwestern Germany. Overall, data obtained from this citizen-science study show that D. reticulatus has significantly expanded its range, especially in northern Germany. Regarding D. marginatus, new locations northwest of the previous range were detected, although the distribution has remained rather stable as compared to D. reticulatus. Especially the spread of D. reticulatus, the vector of Babesia canis, is of major importance for veterinarians and dog owners in terms of canine babesiosis outbreaks or endemisation in hitherto B. canis-free areas. Thus, veterinarians and veterinary students need to be informed about the new situation, to be able to give adequate advice to dog owners on the extended D. reticulatus range and appropriate control measures.